Infrared evidence of NO linkage photoisomerization in Na2[Fe(CN)5NO].2H2O at low temperature - Chacón Villalba, María Elizabeth (1999)
NO effects in biological systems like action in cardiovascular and central nervous system and the genitourinary tract, among others, increase the interest in metal-nitrosyls as NO source [1]. Special interest is centred in sodium nitroprusside dihydrate (Na2[Fe(CN)5NO].2H2O, SNP) which is one of the most studied metal-nitrosyls and used as hypotensive agent [1].